'No Ebola…still doomed' – The Ebola-induced tourism crisis. (May 2018) - Novelli, Marina; Gussing Burgess, Liv; Jones, Adam; Ritchie, Brent W.
Highlights: Explores the indirect spill over effect of a health induced crisis for tourism. Research beyond the immediate response phase into recovery and resolution phases. Employs Rapid Situation Analysis, over a 21 months research timeline. Assesses crisis' planning, response, recovery challenges in a developing country. Abstract: Many recent crisis and disasters affecting tourism have been studied, but few explicitly explore health related crisis in developing countries. This study analyses the effect of the Ebola Virus Disease Epidemic (EVDE) on The Gambia, where, despite no reported cases, EVDE had devastating consequences. A Rapid Situation Analysis is used to gain insights into responses to the EVDE, encompassing interviews with key stakeholders, field observations and follow up meetings with those involved in managing the crisis over 21 months. A crisis and disaster framework is used to understand the challenges encountered. Findings highlight the importance of consumer perception and preparedness and management failures' consequences, contributing to the broader debate on the indirect threat of epidemics on tourism in developing countries.